Toward making the field talk: assessing the relationship between digital technology and sustainable food production in agricultural regions - Khan, Nawab; Xu, Xuanguo; Khayyam, Muhammad; Raziq, Abdul (Frontiers in Nutrition, 2024)
The global food system faces numerous challenges, including population growth, pandemics, climate change, natural disasters, and economic instability. These challenges have a profound impact on agriculture, with climate change leading to unpredictable weather and more frequent extreme events that threaten crop yields and farming sustainability.Farmers are also grappling with rising input costs and market volatility, intensifying the need for improved productivity and efficiency.Purpose: Considering these challenges, digital technology, particularly mobile internet (MI), is emerging as a key tool for achieving sustainable agriculture by enhancing productivity, efficiency, and cost-effectiveness. While much research has focused on the effects of MI on agricultural inputs, prices, and operational efficiency, there is limited understanding of its direct impact on food production outcomes. This study aims to fill this gap by examining the influence of MI usage on crop production.The study utilizes data from 660 farmers across two provinces of Pakistan. Propensity Score Matching (PSM) and linear regression models are employed to assess the impact of MI usage on food production.The analysis reveals a significant positive effect of MI usage on crop production, with MI users experiencing a 14.25% increase in crop yield compared to non-users. The heterogeneity analysis shows varying impacts among different farmer groups: young farmers see a 13.50% increase, less-educated farmers a 15.27% rise, larger-scale farmers a 23.80% boost, and those in economically developed villages a 10.50% improvement per hectare compared to non-users.The study highlights the potential of MI in boosting crop production, particularly for specific farmer demographics. Policymakers should prioritize the development of MI infrastructure in rural areas and collaborate with research institutions, agricultural cooperatives, and enterprises to design interventions, such as financial support and technical assistance, that can help farmers fully leverage the benefits of digital technology.